GE_GERICHTE P/15245/2012 vom 4. März 2014 - GE Cour de justice (2014)
DISPOSITIONS PÉNALES DE LA LCR; VIOLATION DES RÈGLES DE LA CIRCULATION; CONTRAVENTION | CPP.398.4; LCR.90.1; LCR.26.1; LCR.31.1; LCR.34; LCR.36.3; OCR.4.1; OCR.13.2; LCR.39; CP.106